Autotuning GPU Compiler Parameters Using OpenTuner - Bruel, Pedro; Amarís, Marcos; Goldman, Alfredo (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2015: Anais do XVI Simpósio em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad.2015.14268, 2015)
In this paper we implement an autotuner for the compilation ﬂags of GPU algorithms using the OpenTuner framework. An autotuner is a program that ﬁnds a combination of algorithms, or a conﬁguration of an algorithm, that optimizes the solution of a given problem instance or set of instances. We analyse the performance gained after autotuning compilation ﬂags for parallel algorithms in three GPU devices, and show that it is possible to improve upon the high-level optimizations of the CUDA compiler. One of the experimental settings achieved a 30% speedup.